2018
DOI: 10.1128/iai.00173-18
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella Tol-Pal Reduces Outer Membrane Glycerophospholipid Levels for Envelope Homeostasis and Survival during Bacteremia

Abstract: Salmonellae regulate membrane lipids during infection, but the exact proteins and mechanisms that promote their survival during bacteremia remain largely unknown. Mutations in genes encoding the conserved Salmonella enterica serovar Typhimurium (S. Typhimurium) Tol-Pal apparatus caused the outer membrane (OM) sensor lipoprotein, RcsF, to become activated. The capsule activation phenotype for the mutants suggested that Tol-Pal might influence envelope lipid homeostasis. The mechanism involves reducing OM glycer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(56 citation statements)
references
References 66 publications
(112 reference statements)
3
49
0
Order By: Relevance
“…TolB is a soluble periplasmic protein in the Tol-Pal complex, the conserved complex of cell envelopes in Gram-negative bacteria (Lazzaroni et al, 2002). The mutant genotypes of the Tol-Pal proteins vary in length and exhibit some chain reaction compared with the WT in Salmonella typhimurium (Masilamani et al, 2018). In K. pneumoniae, the lengths of each tolB or rcsF overexpression strains were longer than those of the crp strain, indicating that the alteration of cell length in crp was through regulating multiple genes, not just one gene, to adapt to the environment.…”
Section: Discussionmentioning
confidence: 99%
“…TolB is a soluble periplasmic protein in the Tol-Pal complex, the conserved complex of cell envelopes in Gram-negative bacteria (Lazzaroni et al, 2002). The mutant genotypes of the Tol-Pal proteins vary in length and exhibit some chain reaction compared with the WT in Salmonella typhimurium (Masilamani et al, 2018). In K. pneumoniae, the lengths of each tolB or rcsF overexpression strains were longer than those of the crp strain, indicating that the alteration of cell length in crp was through regulating multiple genes, not just one gene, to adapt to the environment.…”
Section: Discussionmentioning
confidence: 99%
“…Using steadystate radioactive labeling of cellular lipids, it was demonstrated that cells lacking the Tol-Pal complex maintain WT levels of LPS but accumulate excess PLs in the OM. This molecular defect, which is also observed in S. Typhimurium (79), likely destabilizes the OM and can potentially account for the OM phenotypes described above. It was further established that PL buildup in the OM in tol-pal mutants is due to defects in retrograde PL transport.…”
Section: The Tol-pal Complexmentioning
confidence: 75%
“…In this study, we have identified suppressor mutations that can rescue OM permeability defects in cells lacking the Tol-Pal complex, which are known to contain excess PLs in their OM (Shrivastava et al, 2017;Masilamani et al, 2018). Mutations in ECA biosynthesis restore OM barrier function, thus blocking entry of large antibiotics and reducing periplasmic leakiness, in tolpal mutant strains (Figs.…”
Section: Discussionmentioning
confidence: 99%